Айтыс жанрында импровизация қубылысы - Матимов, К.Г (SCIENCE and SOCIETY, 2025)
In this article, the genre of saying (aytys) is studied as a special type of literary and musical art of Kara- kalpak folklore. The speech genre is based on improvisation and requires eloquence, ingenuity, and poetic skill from the poet. This genre is said to be an improvisational art that preserves the syncretic features of words, music and movement (acting).
Keywords: literature; folklore; improvisation; improviser; poet